Nano-Doped Monolithic Materials for Molecular Separation - Acquah, C.; Obeng, E.; Agyei, D.; Ongkudon, C.; Loo Chin Moy, Charles; Danquah, Michael (MDPI AG, 2017)
Monoliths are continuous adsorbents that can easily be synthesised to possess tuneable meso-/macropores, convective fluid transport, and a plethora of chemistries for ligand immobilisation. They are grouped into three main classes: organic, inorganic, and hybrid, based on their chemical composition. These classes may also be differentiated by their unique morphological and physicochemical properties which are significantly relevant to their specific separation applications. The potential applications of monoliths for molecular separation have created the need to enhance their characteristic properties including mechanical strength, electrical conductivity, and chemical and thermal stability. An effective approach towards monolith enhancement has been the doping and/or hybridization with miniaturized molecular species of desirable functionalities and characteristics. Nanoparticles are usually preferred as dopants due to their high solid phase dispersion features which are associated with improved intermolecular adsorptive interactions. Examples of such nanomaterials include, but are not limited to, carbon-based, silica-based, gold-based, and alumina nanoparticles. The incorporation of these nanoparticles into monoliths via in situ polymerisation and/or post-modification enhances surface adsorption for activation and ligand immobilisation. Herein, insights into the performance enhancement of monoliths as chromatographic supports by nanoparticles doping are presented. In addition, the potential and characteristics of less common nanoparticle materials such as hydroxyapatite, ceria, hafnia, and germania are discussed. The advantages and challenges of nanoparticle doping of monoliths are also discussed.